Farmakokinetika sulfametoksazol: pengaruh dosis dan kombinasi dengan trimetoprim=The Effect of Doses and Combination with Trimethoprim (TAW) on the Pharmacokinetks of Sulpbametboxazole - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
The effect of doses and combination with trimethoprim (TMP) on the pharmacokinetics of sulphamethoxazole (SMTZ) had been studied in healthy male volunteers. Eight subjects who had agreed to participate the study underwent kinetic trial of SMTZ on four occations, at least one week apart, each after: I(SMTZ 400 mg), II (SMTZ 800 mg), Ill (SMTZ 400 mg+ TMP 80 mg), and IV (SMTZ 800 mg +IMP 160 mg). The doses were administered orally on empty stomach after overnight fasting inform of water suspension. Serial blood samples were drawn immediately before and at 0.00, 0.25, 0.50, 1.00, 1.50, 2.00, 2.50, 3.00, 3.50, 4.00, 6.00, 8.00, 12.00, and 24.00 hours after drug administration. Similarly urine samples were collected at intervals between: 0-4, 4-8, 8-12, 12-24, 24-48, 48-72, and 72-96 hours. Sulphamethorazole concentration were assayed by spectrophotometric methode.Pharmacokinetic parameters were calculated by assuming one compartment open model. Increasing doses of SMTZ from 400 mg to 800 mg reduced the elimination rate of the drug as reflected by a significant reduction in the elimination rate constant, prolongaticlearance (p